Use of simulation models to aid soil and water conservation actions for sustainable agro-forested systems - Duarte, A.C. (2021)
Adequate planning of soil and water conservation requires understanding and prediction of the interactions between soil, climate and management scenarios. These interactions have been investigated over the last decades by means of modelling tools. Some of the most widely used models, namely KINEROS, WEPP, SWAT, and AnnAGNPS have been compared in terms of interfaces, processes, data and parameter requirements, to describe their application domain. Some applicative cases are also added to evidence the importance of rainfall regimes, processes scale, land typologies and management for soil and water conservation modelling, to support the needs of farmers, researchers, extension services and land planners. In general, there is evidence of a large number of parameters to satisfy common users' perception of reliability on simulation results, while they are all good teaching and research tools.